Sclerosing thymoma: A rare case report and brief review of literature. Issue 16 (April 2018) - Li, Xin; Wang, Meng; Sun, Daqiang
Abstract: Rationale: Sclerosing thymoma is an extremely rare mediastinal neoplasm; it was recognized for the first time in 1994 and to date only 15 cases have been reported. Patient concerns: The present study report a case of a 65-year-old man who was incidentally found to have an anterior mediastinal nodule, without clinical symptoms including fever, chest pain, and myasthenia gravis. Diagnoses: The chest computed tomography (CT) revealed the nodule was 4.9 × 4.2 × 3.0 cm in size. And the microscopic and immunohistochemical findings indicated that the final diagnosis was sclerosing thymoma. Interventions: The anterior mediastinal nodule was completely removed. Outcomes: No evidence of recurrence or complication was found in the second year after surgery. Lessons: The biologic behavior of the rare sclerosing thymoma is still largely mysterious; it is utmost importance to classify the sclerosing thymoma from other mediastinal tumors. Its prognosis is favorable and thymectomy is currently the mainstay of treatment.